Study on the exploitation of heterosis for yield and yield contributing traits in sesame (Sesamum indicum L.): Study on the exploitation of heterosis for yield and yield contributing traits in sesame (Sesamum indicum L.) - A M MISAL; P L TAVADARE; R G GAWALI; A R TALAPE (Journal of Oilseeds Research, 2023)
The present investigation was undertaken with the objective to study the magnitude of heterosis involved in 32 hybrids obtained by crossing 4 (female) x 8 (male) genotypes in L x T fashion along with their 12 parents and 2 standard checks (JLT-408 and PRACHI) evaluated during summer 2019-20 at Oilseeds Research Station, Latur. The analysis of variance for experimental design revealed significance differences among the parents, hybrids and parents vs hybrids for most of the characters indicated the presence of genetic variability among the experimental material. The crosses viz., Swetha til x V-25, V-34 x TBS-12, V-32 x TBS-7, Swetha til x R-26 and Swetha til x TBS-12 found with high heterobeltiosis and standard heterosis over check JLT-408 and PRACHI for seed yield along with other yield contributing traits. Significant heterobeltiosis and standard heterosis for seed yield observed for majority of yield and yield attributing traits.